MOURNING AND MELANCHOLIA IN JULIE BUXBAUMâ€™S WHAT TO SAY NEXT NOVEL (PANOPTICON: Journal of English Studies, 2022)
The study aimed to describe the depiction of mourning and melancholia in the novel What to Say Next and to find out the causes of melancholia on character in What to Say Next novel. This study is entitled â€œMourning and Melancholia in Julie Bauxbaumâ€™s What to Say Next Novelâ€. The object of the study is novel by Julie Buxbaum. It described how someone developed mourning and melancholia after the loss of someone loved. This study is sought with qualitative methods in order to reveal the issue of the novel. This study applied the theory of mourning and melancholia by Sigmund Freud (1971). The result of the study should that the main character developed melancholia as portrayed by changed her behavior, aligned herself, blaming herself, having death wishes, and paralysis. It also found that the cause was that she developed melancholia because of the sudden death of her father and loss the family in which her parents were in the middle of divorce before the accident.Keyword: depression, melancholia, mourning, loss